A new path to peaceful union - Hallstein, Walter; India Council for Cultural Relations (London : Asia Publishing House, 1963)
This is a book on the significance of the European Community on the types of civilization and cultural integration taking place in India and the rest of the world
osc 15/01/2019
Loans
Keywords: Economic integration; European Economic Community; European federation; European communities